A phase 1b study of atezolizumab in combination with guadecitabine for the treatment of acute myeloid leukemia. Issue 9 (29th July 2022) - Prebet, Thomas; Goldberg, Aaron D.; Jurcic, Joseph G.; Khaled, Samer; Dail, Monique; Feng, Yuning; Green, Cherie; Li, Chunze; Ma, Connie; Medeiros, Bruno C.; Yan, Mark; Grunwald, Michael R.
Abstract: This phase 1 b study evaluated the safety, efficacy, and pharmacokinetics of atezolizumab in combination with guadecitabine in patients with relapsed/refractory (R/R) or first-line acute myeloid leukemia (AML). Patients received atezolizumab 840 mg (days [D] 8 and 22) and guadecitabine 60 mg/m 2 (D1 and D5) over 28-day cycles. Sixteen patients (median age 73.0 years) enrolled (R/R cohort, n  = 11; first-line cohort, n  = 5). All patients reported at least 1 AE; 15 patients (93.8%) reported grade ≥ 3 AEs, and 15 patients (93.8%) reported SAEs. Fourteen of the 16 patients (87.5%) died during the trial period due to disease progression (8/14) or AEs (6/14), hence the study was terminated early. One patient (from the R/R AML cohort) achieved a response (CR with incomplete platelet recovery) with a DOR of 27.8 months at study termination. Atezolizumab plus guadecitabine had limited clinical activity in AML and an overall unfavorable benefit-risk profile at the investigated dose levels.